2008
DOI: 10.1007/s10265-008-0146-z
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of leaf photosynthesis and simulated individual carbon budget in Primula nutans under contrasting light and temperature conditions

Abstract: Primula nutans Georgi is widely distributed in hummock-and-hollow wetlands on the Qinghai-Tibetan Plateau. To assess the ecophysiology of this species in responding to microenvironments, we examined the photosynthetic characteristics and individual carbon gain of plants growing in different microsites from a hummock-and-hollow wetland on the Qinghai-Tibetan Plateau and under laboratory conditions. Plants from wetland hummock microsites showed significantly higher light-saturated photosynthetic CO(2) uptake (A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…The primary reason may be that the LI stress caused disorder of chloroplast ultrastructure and aggravated its degradation, leading to reduction of chlorophyll content. P max , which was consistent with chlorophyll, decreased under LI, in accordance with Shen et al (2008). The reason may be that low light availability results in significant reduction of carbon gain in the plants.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The primary reason may be that the LI stress caused disorder of chloroplast ultrastructure and aggravated its degradation, leading to reduction of chlorophyll content. P max , which was consistent with chlorophyll, decreased under LI, in accordance with Shen et al (2008). The reason may be that low light availability results in significant reduction of carbon gain in the plants.…”
Section: Discussionsupporting
confidence: 84%
“…Ren et al (2002) have reported that SOD activity of tomato leaves decreased under LI stress. LI also reduced F v /F m , ETR, and --- Ernstsen et al 1999, Andersen and Pedersen 2002, Miko et al 2004, Shen et al 2008. The study has reported that LI stress significantly reduced the chlorophyll content in leaves of Arabidopsis thaliana (Tanaka and Tanaka 2005), henbit genus (Haliapas et al 2008), and rice (Yamazaki 2010).…”
Section: Introductionmentioning
confidence: 89%
“…They also aid in the biological actions for which they are identified in folk medicine. The geographical distribution of plants, affect both the morphology and expression of phytochemicals [24,25] , this may be the case with P. rugelii which lacked tannin, anthraquinone and phenolic compounds. The results of the phytochemical composition of the whole plant powder consisting of the roots, stem and leaves showed that the plant has an appreciable number of phytochemicals.…”
Section: Resultsmentioning
confidence: 99%
“…These differences may be attributed to differences in species as well as the geographical location which is known to affect both the morphology and expression of phytochemicals. [32,33] DPPH is usually used as a reagent to evaluate free radical scavenging activity of antioxidants because it is as table free radical which accepts an electron or hydrogen radical to become a stable diamagnetic molecule. [8] The fruit concentrates exhibit a reasonable antioxidant potential but not statistically significant (P < 0.05) to that of the ascorbic acid standard [ Table 2].…”
Section: Discussionmentioning
confidence: 99%